PENINGKATAN TINDAKAN DALAM PENCARIAN OKNUM TINDAK PIDANA NARKOTIKA - Harry Angga Sinaga (Jurnal Abdi Ilmu, 2020)
Law enforcement of Law Number 31 the Year 1999, aims to restore financial or economic losses to the state as a result of the perpetrators of criminal acts of corruption. If it is viewed from the effectiveness rather than the success in implementing the imposition of the penalty for paying replacement money in a criminal act, it can be said that it has not been effective, especially in the case of the payment of replacement money made by the convicted person. The obstacles faced include, among others, perpetrators of criminal acts of corruption have usually placed funds generated from corruption into a financial system, besides that the perpetrators have also separated their assets through several transactions and have combined the proceeds of corruption in legal business activities. This makes it difficult for the prosecutor to trace the assets of the perpetrators. Based on these conclusions, it can be suggested, that public participation needs to be increased, especially in providing information to law enforcers on the property of convicted corruption cases, as an effort to streamline the payment of replacement money in criminal acts of corruption, it is necessary to immediately formulate a set of regulations that specifically regulate it. regarding the confiscation/confiscation of assets belonging to convicted corruption cases.